Bi-targeting of thioredoxin 1 and telomerase by thiotert promotes cell death of myelodysplastic syndromes and lymphoma - Qiangan Jing; Yunyi Wu; Yanchun Li; Chaoting Zhou; Junyu Zhang; Jun Xia; Keyi Li; Yuhuan Shen; Hongfeng Yao; Xiangmin Tong; Jing Du; Lushan Yu; et al. (Biology Direct)
Abstract Thioredoxin1 (TRX1) and telomerase are both attractive oncology targets that are tightly implicated in tumor initiation and development. Here, we reported that the 6-dithio-2-deoxyguanosine analog thiotert exhibits an effective cytotoxic effect on myelodysplastic syndromes (MDS) cell SKM-1 and lymphoma cell U-937. Further studies confirmed that thiotert effectively disrupts cellular redox homeostasis, as evidenced by elevated intracellular reactive oxygen species (ROS) levels, increased MnSOD, accelerated DNA impairment, and activated apoptosis signal. Mechanistically, our present study revealed that thiotert treatment effectively inhibited the function of the TRX1/TRXR1 system and telomerase reverse transcriptase (TERT), rendering oxidative damage and impairment of telomeres. Meanwhile, pharmacological administration of glutathione (GSH), N-acetylcysteine (NAC), and mitoquinone (MitoQ), or genetic overexpression of TRX1 or TERT in MDS and cells could dampen the toxicity caused by thiotert. Remarkably, the in vivo mouse model of MDS demonstrated that thiotert administration exhibited greater efficacy in tumor reduction compared to the conventional chemotherapy drug cytarabine. Collectively, these results provide experimental insights into the mechanism of thiotert-induced MDS and lymphoma cell death and unveil that thiotert may be an effective and promising new drug for future MDS and lymphoma treatment. Graphical Abstract